SEBS (styrene-ethylene-butylene-styrene) binder, preparation method, application and device thereof

By combining the kettle reactor and the microchannel polymerization reactor in series, combined with the three-kettle continuous hydrogenation process, the problems of long reaction time and complex control in SEBS preparation are solved, and high-quality SEBS binder is efficiently prepared, suitable for electrodes and electrolyte membranes of all-solid lithium-sulfur batteries.

CN119529205AActive Publication Date: 2025-02-28SHENYANG RES INST OF CHEM IND
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411670960.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-28
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

In the prior art, the preparation of SEBS has problems such as long reaction time, complex control technology, strong heat exothermic, and difficult temperature control, resulting in low preparation efficiency and poor product quality.

Method used

SBS was synthesized by active anion polymerization method by combining a kettle reactor, a microchannel polymerization reactor, a delayed tube reactor and a static mixer in series, and SEBS was prepared in a three-kettle continuous hydrogenation process.

Benefits of technology

It realizes efficient preparation of SEBS, with the hydrogenation degree of the product reaching 99.5% to 100%, the molecular weight distribution is narrow, and the structural unit content is suitable. It is suitable for adhesives for all-solid lithium-sulfur battery electrodes and electrolyte membranes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529205A_ABST
    Figure CN119529205A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of thermoplastic elastomer material polymerization and catalytic hydrogenation, and particularly relates to an SEBS binder, a preparation method, application and a device thereof. The preparation method comprises the following steps: carrying out a first-stage polymerization reaction on a styrene solution, a regulator and an initiator, carrying out a second-stage polymerization reaction on the styrene solution and butadiene in a micro-channel reaction unit, carrying out a third-stage polymerization reaction on the styrene solution and styrene in a static mixer 1, and terminating the reaction through an end-capping reagent to obtain an end-capped SBS solution; and mixing the terminated SBS solution with a homogeneous catalyst through a static mixer 2, and introducing the mixture into the autoclave reaction unit for hydrogenation reaction to obtain SEBS (Styrene-Ethylene-Butylene-Styrene). Compared with a traditional intermittent kettle type polymerization and hydrogenation technology, the technology for preparing SBS through continuous polymerization is good in mass and heat transfer and high in efficiency, and the obtained product is excellent in quality. The method has a wide market application and development prospect in industrial continuous preparation of green and high-end SEBS (Styrene-Ethylene-Butylene-Styrene).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of thermoplastic elastomer material polymerization and catalytic hydrogenation, and specifically relates to a SEBS binder, a preparation method and application thereof, and a device thereof. Background Art

[0002] SEBS is a thermoplastic elastomer with a wide range of uses. It is widely used in the shoe industry, road asphalt modification, liquid sealing materials, adhesives, plastic modification, cables, auto parts, medical equipment, etc. At present, there are no reports in the literature and patents on the use of SEBS as a binder for the preparation of all-solid-state lithium-sulfur battery electrodes and electrolyte membranes. SEBS is a saturated SBS. After SBS is synthesized by living anion polymerization, it is moderately hydrogenated in the presence of a catalyst to prepare SEBS.

[0003] Regarding the anionic polymerization method of SBS, the current domestic literature patents are mainly concentrated on the single-pot intermittent polymerization technology. CN118184917A discloses an SBS elastomer and its preparation method and application, CN103374102B discloses a 1,3-conjugated diene / monovinyl aromatic copolymer and its continuous polymerization production method, CN1392166A discloses a preparation method of a styrene-based thermoplastic elastomer, and CN105237696A discloses a novel hydrogenated styrene-butadiene-styrene block copolymer synthesis method. The existing technology has the following deficiencies: the anionic polymerization reaction time is long, the heat release is large, it is difficult to remove, the viscosity is high resulting in low conversion rate, the process initiator is easily deactivated, and gel is easily generated.

[0004] Regarding the homogeneous catalytic hydrogenation modification preparation method of SEBS, the current domestic literature patents are mainly concentrated in the single-pot intermittent hydrogenation and unsaturated polymer continuous hydrogenation technology. Among them, CN105218768A discloses a hydrogenated styrene-butadiene-styrene block copolymer synthesis method, US3696088 discloses a continuous hydrogenation amplification method for unsaturated polymers, CN107099008A discloses a method for continuous hydrogenation of polymers containing olefin unsaturated bonds, and CN105085724A discloses a hydrogenation device and hydrogenation method for continuous hydrogenation of polymers. Different hydrogenation methods use different reactors, different control means and different continuous forms. The following deficiencies exist in the prior art: the hydrogenation reaction time is long and there are many operating steps; at the beginning of the reaction, the heat release is large, difficult to remove, unstable, easy to cross-link to form gel, and the reaction efficiency is low; the energy consumption is large and the control technology is complex; the reactor volume is large, which is not conducive to amplification, and the polymer is easy to decompose; excessive hydrogenation is easy to cause partial catalyst deactivation, etc., affecting the application.

[0005] The existing technology has problems such as long reaction time, complex control technology, strong heat release, and difficult temperature control. The preparation methods have their own advantages and disadvantages. Therefore, in order to obtain SEBS with suitable molecular weight, narrow distribution, and appropriate structural unit content, a better and more efficient preparation method is needed. Summary of the invention

[0006] The purpose of the present invention is to overcome the problems existing in the prior art and to provide a SEBS binder, a preparation method and application thereof and a device thereof.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] After the styrene solution undergoes a first stage polymerization reaction with a regulator and an initiator, the styrene solution undergoes a second stage polymerization reaction with butadiene in a microchannel reaction unit, and then undergoes a third stage polymerization reaction with styrene in a static mixer 1. The reaction is terminated by capping with a capping agent to obtain a capped SBS solution. The capped SBS solution is mixed with a homogeneous hydrogenation catalyst in a static mixer 2, and then introduced into an autoclave reaction unit for a hydrogenation reaction to obtain SEBS.

[0009] Refined styrene and refined butadiene are obtained by refining commercially available styrene and butadiene under reduced pressure to remove trace amounts of water, polymerization inhibitors and other impurities.

[0010] Furthermore, after the styrene solution is subjected to a first stage anionic polymerization reaction with a regulator and an initiator in an autoclave reactor 1, a second stage anionic polymerization reaction is carried out with refined butadiene in a microchannel reaction unit, and a third stage polymerization reaction is carried out with refined styrene in a static mixer 1. The reaction is terminated by end-capping with an end-capping agent in an autoclave reactor 2 to obtain an end-capped SBS solution. The end-capped SBS solution is mixed with a homogeneous hydrogenation catalyst in a static mixer 2, and then introduced into an autoclave reaction unit for hydrogenation reaction to obtain SEBS.

[0011] The specific preparation steps are as follows:

[0012] (1) Anionic polymerization: Styrene solution, regulator and initiator are subjected to a first stage anionic polymerization reaction in a tank reactor 1, and the obtained polystyrene solution and butadiene are simultaneously introduced into a microchannel reaction unit for a second stage anionic polymerization reaction. The second stage anionic polymerization product and styrene are then simultaneously introduced into a static mixer 1 for a third stage anionic polymerization reaction to obtain a reactive SBS solution;

[0013] (2) Hydrogen end-capping reaction: The reactive SBS solution obtained in step (1) enters the autoclave reactor 2, and is subjected to hydrogen end-capping reaction to obtain an end-capped SBS solution;

[0014] (3) Homogeneous catalytic hydrogenation reaction: The blocked SBS solution obtained in step (2) is mixed with a homogeneous hydrogenation catalyst in a static mixer 2, and then introduced into an autoclave reaction unit for hydrogenation reaction to obtain the product SEBS.

[0015] The styrene solution in step (1) is obtained by dissolving styrene in a solvent; the solvent is one or more of alkanes, cycloalkanes and aromatic hydrocarbons; and the molar volume ratio of styrene to the solvent mol:L is (0.2-0.5):(2-3).

[0016] The initiator is one or more of n-butyl lithium, sec-butyl lithium, tert-butyl lithium and isobutyl lithium;

[0017] The regulator is one or more of tetrahydrofuran, diethylene glycol dimethyl ether, tetramethylethylenediamine and ditetrahydrofurfuryl propane;

[0018] The homogeneous hydrogenation catalyst in step (3) is composed of a main catalyst and a co-catalyst; the main catalyst is one of nickel isooctanoate, nickel cyclohexaneate or cobalt cyclohexaneate, the co-catalyst is triisobutylaluminum, and the molar ratio of the main catalyst to the co-catalyst is 1:(1-10).

[0019] In step (1), the autoclave reactor 1 is jacketed in an external circulating water bath at 35°C to 60°C; the reaction time is 20 to 35 minutes;

[0020] The microchannel reaction unit is placed in a water bath at 55°C to 80°C; the reaction time is 15 to 40 minutes;

[0021] The static mixer 1 is placed in a water bath at 55°C to 80°C; the reaction time is 15 to 30 minutes;

[0022] In step (2), the autoclave reactor 2 is jacketed in an external circulating water bath at 50°C to 70°C; the reaction time is 10 to 20 minutes;

[0023] In step (3): static mixer 2 is placed in a water bath at 55°C to 70°C; the mixing time is 3-5 min;

[0024] The jacket of the autoclave reaction unit is placed in an external circulating water bath at 60°C to 80°C; the reaction time is 30 to 90 minutes.

[0025] In the first stage of anionic polymerization in step (1), the molar ratio of styrene: regulator: initiator is (0.2-0.5): (0.0002-0.05): (0.001-0.006), preferably, the molar ratio of styrene: regulator: initiator is (0.2-0.5): (0.01-0.05): (0.001-0.006); the molar ratio of styrene in the first stage of anionic polymerization: butadiene in the second stage of anionic polymerization: styrene in the third stage of anionic polymerization is 1: (7-10): 1;

[0026] In step (2), the hydrogen pressure is 0.40-0.90 MPa;

[0027] In step (3), the amount of catalyst added is 0.5-5 mmol (Ni or Co) / 100 g SBS; hydrogen is introduced from the bottom of the autoclave 3, the hydrogen flow rate is 0.8-2.4 L / h, and the hydrogen pressure is 1.60-3.00 MPa.

[0028] The molecular weight (Mn) of the SBS prepared in step (1) is 100,000 to 330,000; the molecular weight distribution is 1.01 to 1.20; the St (styrene) content is 26.0 to 35.0 weight percent; the Bd (butadiene) content is 65.0 to 74.0 weight percent, wherein the content of 1,2-Bd (butadiene) structural units is 34.0 to 44.0 weight percent, and the content of 1,4-Bd (butadiene) structural units is 56.0 to 66.0 weight percent;

[0029] The degree of hydrogenation of the SEBS obtained in step (3) is 99.5% to 100%.

[0030] A SEBS adhesive prepared according to the preparation method.

[0031] Application of SEBS binder in the preparation of all-solid-state lithium-sulfur battery electrodes and electrolyte membranes.

[0032] The continuous device used in the preparation method comprises a kettle reactor 1, a microchannel reaction unit, a static mixer 1, a kettle reactor 2, a static mixer 2, a high-pressure reactor unit, and a buffer tank 1 which are connected in sequence.

[0033] The microchannel reaction unit is composed of a microchannel polymerization reactor 1 and a time-delay tube reactor 1 connected in series; the autoclave reaction unit is composed of an autoclave 1, an autoclave 2 and an autoclave 3 connected in series.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] The present invention proposes to use a kettle reactor, a microchannel polymerization reactor, a time-delayed tube reactor and a static mixer in series combination, synthesize SBS by an active anion polymerization method, and prepare SEBS as a binder for all-solid-state lithium-sulfur battery electrodes and electrolyte membranes through three-kettle continuous hydrogenation. High-performance SEBS is obtained by polymerization and hydrogenation with styrene and butadiene as monomers using different initiators, regulators and catalysts, and the hydrogenation degree of the obtained SEBS is 99.5% to 100%. SEBS is used as a binder to prepare a solid electrolyte membrane with high ionic conductivity through a slurry coating process, forming a close contact and good bonding mixed system, which is flexible and has a low swelling rate, and is suitable for the current development needs of binders. The continuous polymerization preparation technology of the present invention has better mass and heat transfer than the traditional intermittent kettle polymerization and hydrogenation technology, high efficiency, and the obtained product is of excellent quality. It has broad market application and development prospects in the continuous preparation of "green, high-end SEBS" in industry.

[0036] The present invention solves the problems of strong heat release, slow and difficult removal, difficult temperature control, long reaction time, etc. in the initial stage of anion reaction process of small molecular weight polymers at the microchannel scale, and can make the polystyrene solution fully contact with refined butadiene at the microchannel scale; solves the problems of strong heat release, difficult temperature control, easy cross-linking of polymers in the initial stage of single-pot hydrogenation reaction process under the three-pot continuous hydrogenation process, and can make the homogeneous catalyst and SBS solution react mildly under the action of hydrogen environment, significantly improve the reaction efficiency and process product quality, realize continuity, and reach the designable molecular weight and hydrogenation degree. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0038] The specific embodiments of the present invention are further described below with reference to examples. It should be noted that the specific embodiments described here are only for illustration and explanation of the present invention and are not limited to the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not described in detail are all process steps or preparation methods known to those skilled in the art.

[0039] The kettle reactor 1 of the present invention is an anchor kettle reactor; the kettle reactor 2 is a self-priming propulsion kettle reactor; the microchannel polymerization reactor 1 is an impinging flow reactor; the delay tube reactor 1 is a coil tube reactor; the autoclave 1 and the autoclave 2 are both self-priming propulsion autoclave reactors; the autoclave 3 is a plug flow autoclave reactor, and the reaction devices of the present invention can all be purchased commercially.

[0040] Refined styrene and refined butadiene are obtained by refining commercially available styrene and butadiene under reduced pressure to remove trace amounts of water, polymerization inhibitors and other impurities.

[0041] Example 1

[0042] (1) 46.2 g of purified styrene, 1718.0 g of a mixed solvent of cyclohexane (1030.8 g) and benzene (687.2 g) (mixing ratio of 6:4) were added to a tank reactor 1. 3.7 mL of tetrahydrofuran and 1.4 mL of tetramethylethylenediamine (5% by mass cyclohexane solution) were added to the tank reactor 1. 1.8 mL of 1.3 M sec-butyl lithium (sec-butyl lithium hexane solution) initiator was added to the autoclave reactor 1 to initiate the polymerization reaction. The autoclave reactor 1 was jacketed in an external circulating water bath at 40° C. The polymerization reaction was carried out for 25 min to obtain a polystyrene solution. The polystyrene solution and 213.2 g of refined butadiene were metered into a microchannel reaction unit consisting of a microchannel polymerization reactor 1 and a time-delayed tube reactor 1 in series in two ways using a metering pump and a micrometering pump for reaction. The microchannel polymerization reactor 1 and the time-delayed tube reactor 1 were placed in a 72° C. water bath. The second stage of anionic polymerization was carried out in the microchannel polymerization reactor 1 and the time-delayed tube reactor 1 using the efficient mixed mass transfer and heat transfer characteristics of the microchannel. The residence time of the solution in the microchannel reaction unit was 24. .0min; use a micro-metering pump to mix 44.7g of refined styrene at the end of the delay tube reactor 1 with the solution generated by the microchannel reaction unit and enter the static mixer 1 for the third stage of anionic polymerization reaction. The static mixer 1 is placed in a 72°C water bath. The residence time of the solution in the static mixer 1 is 27.0min, and a 14.9wt% SBS solution with reaction activity is obtained (the styrene content is 29.9wt%, the butadiene content is 70.1wt%; wherein the content of 1,2-structural units in butadiene is 39.2wt%, and the content of 1,4-structural units is 60.8wt%), the solution viscosity is 1255cps, the molecular weight is 236063, and the distribution is 1.07; the product enters the autoclave reactor 2.

[0043] (2) The SBS solution in the autoclave reactor 2 was subjected to a capping termination reaction under 0.6 MPa low-pressure hydrogen. The autoclave reactor 2 was jacketed in an external circulating water bath at 60° C., and the capping termination reaction was carried out for 15 minutes.

[0044] (3) The blocked SBS solution and the nickel-based (nickel cyclohexane acid and triisobutyl aluminum molar ratio of 1:3) catalyst (catalyst addition amount of 0.16gNi / 100gSBS) were metered by a metering pump and a micro-metering pump in two ways, mixed by a static mixer 2, and then entered a reactor consisting of autoclave 1, autoclave 2 and autoclave 3 in series for hydrogenation reaction; static mixer 2 was placed in a 60°C water bath, and the residence time of the solution in static mixer 2 was 3min; autoclave 1, autoclave 2, and autoclave 3 were jacketed in a 70°C external circulation water bath, and the total residence time in the autoclave reaction unit was 41min. Hydrogen was introduced from the bottom of autoclave 3, the hydrogen flow rate was 1.2L / h, and the hydrogen pressure was 1.90MPa. The product entered a buffer tank 1, and then was oxidized by 8wt% hydrogen peroxide solution, pickled with citric acid (citric acid can be replaced by sebacic acid or adipic acid), centrifugal desalting, alkali washing, centrifugal dehydration, wet condensation, and drying to obtain 183.2g hydrogenation degree ( 1 H-NMR test analysis, calculated based on the spectrum) 99.7% SEBS dry glue.

[0045] Example 2

[0046] (1) 45.7 g of purified styrene and 1744.0 g of cyclohexane were added to a tank reactor 1. 3.1 mL of tetrahydrofuran and 2.3 mL of tetramethylethylenediamine (a cyclohexane solution with a mass fraction of 5%) were added to the tank reactor 1. 2.0 mL of 1.6 M n-butyl lithium (n-butyl lithium hexane solution) initiator was added to the autoclave reactor 1 to initiate the polymerization reaction, and the autoclave reactor 1 was jacketed in an external circulation water bath at 45° C. The polymerization reaction was carried out for 22 minutes to obtain a polystyrene solution; the polystyrene solution and 210.5 g of refined butadiene were metered into a microchannel reaction unit consisting of a microchannel polymerization reactor 1 and a time-delayed tube reactor 1 in series in two ways using a metering pump and a micrometering pump for reaction, the microchannel polymerization reactor 1 and the time-delayed tube reactor 1 were placed in a 75° C. water bath, and the second stage of anionic polymerization was carried out in the microchannel polymerization reactor 1 and the time-delayed tube reactor 1 using the efficient mixed mass transfer and heat transfer characteristics of the microchannel, and the residence time of the solution in the microchannel reaction unit was 21. .5min; use a micro-metering pump to mix 45.0g of refined styrene at the end of the delay tube reactor 1 with the solution generated by the microchannel reaction unit and enter the static mixer 1 for the third stage of anionic polymerization reaction. The static mixer 1 is placed in a 75°C water bath. The residence time of the solution in the static mixer 1 is 23.5min, and a 14.6wt% SBS solution with reaction activity is obtained (the styrene content is 30.1wt%, the butadiene content is 69.9wt%; wherein the content of 1,2-structural units in butadiene is 41.8wt%, and the content of 1,4-structural units is 58.2wt%), the solution viscosity is 1060cps, the molecular weight is 174530, and the distribution is 1.09; the product enters the autoclave reactor 2.

[0047] Steps (2) and (3) are the same as those in Example 1 to obtain 210.0 g of hydrogenation degree ( 1 H-NMR test analysis, calculated based on the spectrum) 99.5% SEBS dry glue.

[0048] Example 3

[0049] (1) 45.0 g of purified styrene, 1720.0 g of a mixed solvent of cyclohexane (1032.0 g) and hexane (688.0 g) (mixing ratio of 6:4) were added to the autoclave reactor 1. 3.5 mL of ditetrahydrofurfuryl propane (cyclohexane solution with a mass fraction of 5%) was added to the autoclave reactor 1. 3.6 mL of 1.6 M n-butyl lithium (n-butyl lithium hexane solution) initiator was added to the autoclave reactor 1 to initiate the polymerization reaction. The autoclave reactor 1 was jacketed in an external circulating water bath at 45° C. The polymerization reaction was carried out for 20 min to obtain a polystyrene solution. The polystyrene solution and 212.6 g of refined butadiene were metered into a microchannel reaction unit consisting of a microchannel polymerization reactor 1 and a time-delayed tube reactor 1 in series in two ways using a metering pump and a micrometering pump for reaction. The microchannel polymerization reactor 1 and the time-delayed tube reactor 1 were placed in a 70° C. water bath. The second stage of anionic polymerization was carried out in the microchannel polymerization reactor 1 and the time-delayed tube reactor 1 using the efficient mixed mass transfer and heat transfer characteristics of the microchannel. The residence time of the solution in the microchannel reaction unit was 17 .5min; use a micro-metering pump to mix 47.2g of refined styrene at the end of the delay tube reactor 1 with the solution generated by the microchannel reaction unit and enter the static mixer 1 for the third stage of anionic polymerization reaction. The static mixer 1 is placed in a 70°C water bath. The residence time of the solution in the static mixer 1 is 18.5min, and a 15.04wt% SBS solution with reaction activity is obtained (the styrene content is 30.2wt%, the butadiene content is 69.8wt%; wherein the content of 1,2-structural units in butadiene is 39.7wt%, and the content of 1,4-structural units is 60.3wt%), the solution viscosity is 750cps, the molecular weight is 110530, and the distribution is 1.04; the product enters the autoclave reactor 2.

[0050] Steps (2) and (3) are the same as those in Example 1 to obtain 225.3 g of hydrogenation degree ( 1 H-NMR test analysis, calculated based on the spectrum) 99.9% SEBS dry glue.

[0051] Example 4

[0052] (1) 43.2 g of purified styrene, 1704.0 g of a mixed solvent of cyclohexane (852.0 g) and benzene (852.0 g) (mixing ratio of 5:5) were added to a tank reactor 1. 2.9 mL of tetrahydrofuran was added to the tank reactor 1. 1.4 mL of 1.3 M sec-butyl lithium (sec-butyl lithium hexane solution) initiator was added to the autoclave reactor 1 to initiate the polymerization reaction. The autoclave reactor 1 was jacketed in an external circulation water bath at 45° C. The polymerization reaction was carried out for 27.5 min to obtain a polystyrene solution. The polystyrene solution and 208.7 g of refined butadiene were metered into a microchannel reaction unit consisting of a microchannel polymerization reactor 1 and a time-delay tube reactor 1 in series in two ways using a metering pump and a micrometering pump for reaction. The microchannel polymerization reactor 1 and the time-delay tube reactor 1 were placed in a water bath at 80° C. The second stage of anionic polymerization was carried out in the microchannel polymerization reactor 1 and the time-delay tube reactor 1 using the efficient mixed mass transfer and heat transfer characteristics of the microchannel. The residence time of the solution in the microchannel reaction unit was 2 8.0min; 45.9g of refined styrene was mixed with the solution generated by the microchannel reaction unit at the end of the delay tube reactor 1 by a micro-metering pump and entered into the static mixer 1 for the third stage of anionic polymerization reaction. The static mixer 1 was placed in a water bath at 80°C. The residence time of the solution in the static mixer 1 was 27.5min, and a 14.8wt% SBS solution with reaction activity was obtained (the styrene content was 29.8wt%, the butadiene content was 70.2wt%; the content of 1,2-structural units in butadiene was 34.4wt%, and the content of 1,4-structural units was 65.6wt%), the solution viscosity was 2830cps, the molecular weight was 294033, and the distribution was 1.10; the product entered into the autoclave reactor 2.

[0053] (2) The SBS solution in the autoclave reactor 2 was subjected to a capping termination reaction under 0.7 MPa low-pressure hydrogen. The autoclave reactor 2 was jacketed in an external circulating water bath at 65° C., and the capping termination reaction was carried out for 18 min.

[0054] (3) The blocked SBS solution and the nickel-based (nickel isooctanoate to triisobutylaluminum molar ratio of 1:2.5) catalyst (catalyst addition amount of 0.20 g Ni / 100 g SBS) were metered by a metering pump and a micro-metering pump in two ways, mixed by a static mixer 2, and then entered a reactor consisting of autoclave 1, autoclave 2 and autoclave 3 in series for hydrogenation reaction; the static mixer 2 was placed in a 60° C. water bath, and the residence time of the solution in the static mixer 2 was 3 min; the autoclaves 1, 2 and 3 were jacketed in an external circulating water bath at 75° C., and the total residence time in the autoclave reaction unit was 50 min. Hydrogen was introduced from the bottom of the autoclave 3, the hydrogen flow rate was 1.5 L / h, and the hydrogen pressure was 2.30 MPa. The product entered a buffer tank 1, and then was oxidized with 8 wt % hydrogen peroxide solution, washed with citric acid, centrifuged for desalination, alkaline washed, centrifuged for dehydration, wet condensed, and dried to obtain 169.4 g of hydrogenated product with a degree of hydrogenation ( 1 H-NMR test analysis, calculated according to the spectrum) 100.0% SEBS dry glue.

[0055] Example 5

[0056] (1) 46.9 g of purified styrene and 1754.0 g of cyclohexane were added to a tank reactor 1. 3.7 mL of tetrahydrofuran and 1.5 mL of diethylene glycol dimethyl ether (a cyclohexane solution with a mass fraction of 5%) were added to the tank reactor 1. 1.8 mL of 1.3 M sec-butyl lithium (sec-butyl lithium hexane solution) initiator was added to the autoclave reactor 1 to initiate the polymerization reaction. The autoclave reactor 1 was jacketed in an external circulating water bath at 40° C. The polymerization reaction was carried out for 25 min to obtain a polystyrene solution. The polystyrene solution and 206.4 g of refined butadiene were metered into a microchannel reaction unit consisting of a microchannel polymerization reactor 1 and a time-delay tube reactor 1 in series in two ways using a metering pump and a micrometering pump for reaction. The microchannel polymerization reactor 1 and the time-delay tube reactor 1 were placed in a 70° C. water bath. The second stage of anionic polymerization was carried out in the microchannel polymerization reactor 1 and the time-delay tube reactor 1 using the efficient mixed mass transfer and heat transfer characteristics of the microchannel. The residence time of the solution in the microchannel reaction unit was 25 .5min; use a micro-metering pump to mix 43.0g of refined styrene at the end of the delay tube reactor 1 with the solution generated by the microchannel reaction unit and enter the static mixer 1 for the third stage of anionic polymerization reaction. The static mixer 1 is placed in a 70°C water bath. The residence time of the solution in the static mixer 1 is 25.0min, and a 14.4wt% SBS solution with reaction activity is obtained (the styrene content is 30.2wt%, the butadiene content is 69.8wt%; wherein the content of 1,2-structural units in butadiene is 42.1wt%, and the content of 1,4-structural units is 57.9wt%), the solution viscosity is 1543cps, the molecular weight is 254908, and the distribution is 1.08; the product enters the autoclave reactor 2.

[0057] Steps (2) and (3) are the same as those in Example 1 to obtain 190.9 g of hydrogenation degree ( 1 H-NMR test analysis, calculated based on the spectrum) 99.9% SEBS dry glue.

[0058] Example 6

[0059] (1) 33.2 g of purified styrene, 1832.0 g of a mixed solvent of cyclohexane (916.0 g) and benzene (916.0 g) (mixing ratio of 5:4) were added to a tank reactor 1. 2.4 mL of tetrahydrofuran and 1.5 mL of tetramethylethylenediamine (5% by mass cyclohexane solution) were added to the tank reactor 1. 1.2 mL of 1.3 M sec-butyl lithium (sec-butyl lithium hexane solution) initiator was added to the autoclave reactor 1 to initiate the polymerization reaction. The autoclave reactor 1 was jacketed in an external circulating water bath at 40° C. The polymerization reaction was carried out for 20 min to obtain a polystyrene solution. The polystyrene solution and 136.5 g of refined butadiene were metered into a microchannel reaction unit consisting of a microchannel polymerization reactor 1 and a time-delay tube reactor 1 in series in two ways using a metering pump and a micrometering pump for reaction. The microchannel polymerization reactor 1 and the time-delay tube reactor 1 were placed in a 70° C. water bath. The second stage of anionic polymerization was carried out in the microchannel polymerization reactor 1 and the time-delay tube reactor 1 using the efficient mixed mass transfer and heat transfer characteristics of the microchannel. The residence time of the solution in the microchannel reaction unit was 1. 8.0min; 32.0g of refined styrene was mixed with the solution generated by the microchannel reaction unit at the end of the delay tube reactor 1 by a micro-metering pump and entered into the static mixer 1 for the third stage of anionic polymerization reaction. The static mixer 1 was placed in a 70°C water bath. The residence time of the solution in the static mixer 1 was 16.5min to obtain a 9.8wt% SBS solution with reaction activity (styrene content was 32.2wt%, butadiene content was 67.8wt%; wherein the content of 1,2-structural units in butadiene was 43.6wt%, and the content of 1,4-structural units was 56.4wt%), the solution viscosity was 302cps, the molecular weight was 218054, and the distribution was 1.05; the product entered into the autoclave reactor 2.

[0060] (2) Step (2) is the same as step (2) in Example 1.

[0061] (3) The blocked SBS solution and the cobalt-based (cobalt cyclohexane acid and triisobutyl aluminum molar ratio of 1:1.2) catalyst (catalyst addition amount of 0.08gCo / 100gSBS) were metered by a metering pump and a micro-metering pump in two ways, mixed by a static mixer 2, and then entered a reactor consisting of autoclave 1, autoclave 2 and autoclave 3 in series for hydrogenation reaction; the static mixer 2 was placed in a 60°C water bath, and the residence time of the solution in the static mixer 2 was 3min; the autoclaves 1, 2 and 3 were jacketed in a 70°C external circulation water bath, and the total residence time in the autoclave reaction unit was 34.5min. Hydrogen was introduced from the bottom of the autoclave 3, the hydrogen flow rate was 0.9L / h, and the hydrogen pressure was 2.50MPa. The product entered the buffer tank 1, and then was oxidized by 8wt% hydrogen peroxide solution, washed with citric acid, centrifugal desalting, alkali washing, centrifugal dehydration, wet condensation, and dried to obtain 138.9g hydrogenation degree ( 1 H-NMR test analysis, calculated based on the spectrum) 99.7% SEBS dry glue.

[0062] Comparative Example 1

[0063] The difference between Comparative Example 1 and Example 1 is that all the anionic polymerization steps and hydrogen end-capping termination reaction steps in Example 1 are carried out in the same conventional polymerization reactor, and all the homogeneous catalytic hydrogenation reaction steps are carried out in a conventional high-pressure hydrogenation reactor; the total anionic polymerization reaction time is 150 min, the hydrogen end-capping termination reaction time is 15 min, and the total homogeneous catalytic hydrogenation reaction time is 120 min; the anionic polymerization reaction obtains a 15.0 wt% reactive SBS solution (the styrene content is 30.1 wt%, the butadiene content is 69.9 wt%; wherein the content of 1,2-structural units in butadiene is 38.7 wt%, and the content of 1,4-structural units is 61.3 wt%), the solution viscosity is 1301 cps, the molecular weight is 239940, and the distribution is 1.12; and then subjected to hydrogenation modification reaction, 190.4 g of hydrogenation degree ( 1 H-NMR test analysis, calculated based on the spectrum) 98.9% SEBS dry glue.

[0064] Comparative Example 2

[0065] The steps of anionic polymerization and hydrogen end-capping termination reaction are the same as those in Example 6. The difference between Comparative Example 2 and Example 6 is that: the anionic polymerization reaction obtains 9.8wt% of SBS solution with reaction activity (styrene content is 31.9wt%, butadiene content is 68.1wt%; wherein the content of 1,2-structural units in butadiene is 43.0wt%, and the content of 1,4-structural units is 57.0wt%), the solution viscosity is 289cps, the molecular weight is 214664, and the distribution is 1.05; when performing the hydrogenation modification reaction, the autoclave 1, the autoclave 2, and the autoclave 3 are jacketed in an external circulating water bath at 40°C to obtain 145.9g of hydrogenation degree ( 1 H-NMR test analysis, calculated based on the spectrum) 84.1% of SEBS dry glue.

[0066] Comparative Example 3

[0067] The steps of anionic polymerization and hydrogen end-capping termination reaction are the same as those in Example 6. The difference between Comparative Example 3 and Example 6 is that: the anionic polymerization reaction obtains 9.8wt% of SBS solution with reaction activity (styrene content is 31.9wt%, butadiene content is 68.1wt%; wherein the content of 1,2-structural units in butadiene is 43.0wt%, and the content of 1,4-structural units is 57.0wt%), the solution viscosity is 270cps, the molecular weight is 210058, and the distribution is 1.06; when the hydrogenation modification reaction is carried out, the total residence time in the autoclave reaction unit is 20.0min, and 140.6g of hydrogenation degree ( 1 H-NMR test analysis, calculated based on the spectrum) 80.9% of SEBS dry glue.

[0068] Comparative Example 4

[0069] The steps of anionic polymerization and hydrogen end-capping termination reaction are the same as those in Example 1. The difference between Comparative Example 4 and Example 1 is that the feeding ratio of styrene and butadiene is changed, and the mass ratio of styrene in the first stage reaction: butadiene in the second stage reaction: styrene in the third stage reaction is 23.0:54.0:23.0. The anionic polymerization reaction obtains 14.8wt% of SBS solution with reaction activity (styrene content is 45.8wt%, butadiene content is 54.2wt%; wherein the content of 1,2-structural units in butadiene is 41.9wt%, and the content of 1,4-structural units is 58.1wt%), the solution viscosity is 1233cps, the molecular weight is 231205, and the distribution is 1.08; after hydrogenation modification reaction, 177.9g hydrogenation degree ( 1 H-NMR test analysis, calculated based on the spectrum) 99.6% of SEBS dry glue. Solid electrolyte membrane preparation and wet processing conditions

[0070] Preparation conditions and configuration ratio:

[0071] Preparation conditions:

[0072] Dissolve SEBS powder in xylene, toluene or benzene to prepare a certain concentration of bonding system, and then 10 Si 0.3 PS 6.7 Cl 1.8 The (LiSiPSCl) solid electrolyte powder is mixed with the binding system, xylene, toluene or benzene is added to adjust the viscosity, and the mixture is dispersed and stirred at high speed for 20 to 30 minutes. The slurry is evenly coated on a stainless steel test sample and dried at 60°C to 80°C for 24 hours to remove the system solvent.

[0073] Configuration ratio:

[0074] Examples 1 to 6 and Comparative Examples 1 to 4 were used as binders to prepare solid electrolyte membranes through a slurry coating process: 100 parts of LiSiPSCl; 25 parts of benzene, 25 parts of xylene; 3 parts of binder SEBS.

[0075] Comparative Example 5: 100 parts of LiSiPSCl; 25 parts of benzene, 25 parts of xylene; 3 parts of commercially available nitrile rubber (NBR) binder (Ningbo Shunze Rubber Co., Ltd.).

[0076] Comparative Example 6: 100 parts of LiSiPSCl; 25 parts of benzene, 25 parts of xylene; 3 parts of commercially available polyvinylidene fluoride (PVDF) binder (Shanghai Duoyuan Plastic Raw Materials Co., Ltd.).

[0077] Mechanical and electrochemical properties characterization

[0078] The mechanical properties, constant current charge and discharge test and AC impedance test of the solid electrolyte membrane are tested in accordance with relevant national standards and enterprise standards.

[0079] Constant current charge and discharge test: Use CT 2001A LAND micro / small current tester, the test voltage range is 0.9~2.4V. During the cycle, discharge first and then charge.

[0080] AC impedance test: Autolab PGSTAT302N electrochemical workstation was used, the test conditions were temperature 25°C, sine wave amplitude 5mV, frequency setting interval 10 6 ~10 -1 Hz.

[0081] The electrochemical performance test results of the solid electrolyte membrane are shown in Table 1.

[0082] Table 1 Electrochemical performance test results of solid electrolyte membrane

[0083]

[0084] It can be seen from Table 1 that, under the same addition amount, the solid electrolyte membrane prepared by using SEBS as a binder in the embodiment of the present invention has greater adhesion, better flexibility and film-forming properties, higher ionic conductivity, and lower electrolyte swelling rate, so that the overall performance of the electrolyte membrane is optimal. In addition, the first discharge specific capacity of the all-solid-state lithium battery assembled with the electrolyte membrane is also higher than that of similar products on the market. The styrene content in the SEBS binder prepared in Comparative Example 4 is higher, showing greater rigidity, poor flexibility and film-forming properties, which is not conducive to dispersion and uneven distribution, affecting the ionic conductivity after film formation.

[0085] From the overall examples, SEBS binder with high number average molecular weight (large Mn) is better than SEBS binder with low number average molecular weight (small Mn); SEBS binder with high degree of hydrogenation is better than SEBS binder with low degree of hydrogenation; at the same time, compared with the commercial binder added to comparative examples 5 and 6, the adhesion, toughness and ionic conductivity of the electrolyte membranes of Examples 1-6 are better than those of the solid electrolyte membranes added with commercially available binders.

[0086] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A continuous preparation method of a SEBS binder, characterized in that: After the styrene solution undergoes a first stage polymerization reaction with a regulator and an initiator, the styrene solution undergoes a second stage polymerization reaction with refined butadiene in a microchannel reaction unit, and then undergoes a third stage polymerization reaction with refined styrene in a static mixer 1. The reaction is terminated by end-capping with an end-capping agent to obtain an end-capped SBS solution. The end-capped SBS solution is mixed with a homogeneous hydrogenation catalyst in a static mixer 2, and then introduced into an autoclave reaction unit for a hydrogenation reaction to obtain SEBS.

2. The continuous preparation method of SEBS binder according to claim 1, characterized in that: The following steps are involved: (1) Anionic polymerization: A styrene solution, a regulator and an initiator are subjected to a first stage anionic polymerization reaction in a tank reactor 1, and the obtained polystyrene solution and refined butadiene are simultaneously introduced into a microchannel reaction unit for a second stage anionic polymerization reaction. The second stage anionic polymerization product and refined styrene are then simultaneously introduced into a static mixer 1 for a third stage anionic polymerization reaction to obtain a reactive SBS solution; (2) Hydrogen end-capping reaction: The reactive SBS solution obtained in step (1) enters the autoclave reactor 2, and is subjected to hydrogen end-capping reaction to obtain an end-capped SBS solution; (3) Homogeneous catalytic hydrogenation reaction: The blocked SBS solution obtained in step (2) is mixed with a homogeneous hydrogenation catalyst in a static mixer 2, and then introduced into an autoclave reaction unit for hydrogenation reaction to obtain the product SEBS.

3. The continuous preparation method of SEBS binder according to claim 2, characterized in that: The styrene solution in step (1) is obtained by dissolving styrene in a solvent; the solvent is one or more of alkanes, cycloalkanes and aromatic hydrocarbons; The initiator is one or more of n-butyl lithium, sec-butyl lithium, tert-butyl lithium and isobutyl lithium; The regulator is one or more of tetrahydrofuran, diethylene glycol dimethyl ether, tetramethylethylenediamine and ditetrahydrofurfuryl propane; The homogeneous hydrogenation catalyst in step (3) is composed of a main catalyst and a co-catalyst; the main catalyst is one of nickel isooctanoate, nickel cyclohexaneate or cobalt cyclohexaneate, the co-catalyst is triisobutylaluminum, and the molar ratio of the main catalyst to the co-catalyst is 1:(1-10).

4. The continuous preparation method of SEBS binder according to claim 2, characterized in that: In step (1), the autoclave reactor 1 is jacketed in an external circulating water bath at 35°C to 60°C; the reaction time is 20 to 35 minutes; The microchannel reaction unit is placed in a water bath at 55°C to 80°C; the reaction time is 15 to 40 minutes; The static mixer 1 is placed in a water bath at 55°C to 80°C; the reaction time is 15 to 30 minutes; In step (2), the autoclave reactor 2 is jacketed in an external circulating water bath at 50 to 70° C.; the reaction time is 10 to 20 min; In step (3): static mixer 2 is placed in a water bath at 55°C to 70°C; the mixing time is 3-5 min; The jacket of the autoclave reaction unit is placed in an external circulating water bath at 60°C to 80°C; the reaction time is 30 to 90 minutes.

5. The continuous preparation method of SEBS binder according to claim 2, characterized in that: In the first stage of anionic polymerization in step (1), the molar ratio of styrene: regulator: initiator is: (0.2-0.5): (0.0002-0.05): (0.001-0.006); the molar ratio of styrene in the first stage of anionic polymerization: butadiene in the second stage of anionic polymerization: styrene in the third stage of anionic polymerization is 1: (7-10): 1; In step (2), the hydrogen pressure is 0.40-0.90 MPa; In step (3), the amount of catalyst added is 0.5-5 mmol Ni or Co / 100 g SBS; the hydrogen flow rate is 0.8-2.4 L / h, and the hydrogen pressure is 1.60-3.00 MPa.

6. The continuous preparation method of SEBS binder according to claim 5, characterized in that: The molecular weight Mn of the SBS prepared in step (1) is 100000-330000; the molecular weight distribution is 1.01-1.20; the St styrene content is 26.0-35.0 wt%; the Bd butadiene content is 65.0-74.0 wt%, wherein the content of 1,2-Bd butadiene structural units is 34.0-44.0 wt%, and the content of 1,4-Bd butadiene structural units is 56.0-66.0 wt%; The degree of hydrogenation of the SEBS obtained in step (3) is 99.5% to 100%.

7. A SEBS binder prepared according to the preparation method according to any one of claims 1 to 6.

8. An application of the SEBS adhesive according to claim 7, characterized in that: Application of SEBS binder in the preparation of all-solid-state lithium-sulfur battery electrodes and electrolyte membranes.

9. A continuous device used in the preparation method according to claim 1, comprising a kettle reactor 1, a microchannel reaction unit, a static mixer 1, a kettle reactor 2, a static mixer 2, a high-pressure reactor unit, and a buffer tank 1 connected in sequence.

10. The continuous device according to claim 9, characterized in that: The microchannel reaction unit is composed of a microchannel polymerization reactor 1 and a time-delay tube reactor 1 connected in series; the autoclave reaction unit is composed of an autoclave 1, an autoclave 2 and an autoclave 3 connected in series.

Citation Information

Patent Citations

  • Production method of 1,3-conjugated diene / monovinyl aromatic copolymer and its continuous polymerization

    CN103374102B

  • Hydrogenation device and hydrogenation method for polymer continuous hydrogenation

    CN105085724A

  • Method for synthesizing hydrogenated styrene-butadiene-styrene segmented copolymer

    CN105218768A

  • Novel hydrogenated styrene-butadiene-styrene segmented copolymer synthesis method

    CN105237696A

  • A hydrogenation method for a polymer comprising an olefin unsaturated bond

    CN107099008A